Analysis of Illocutionary Speech Acts on Dilan's Character in the Movie: Dilan 1990 - Bangol, Riniati; Danial, Alysa Fadillah A.; Hasan, Alvin R.; Polingala, Elsa (Journal of Advance in Language, Literature, and Education, 2025)
In the film Dilan 1990 through a pragmatic approach based on the theory of speech acts proposed by John Searle. Illocutionary speech acts play an important role in interpersonal communication because they reflect the speaker’s intentions and communication strategies in interacting with the interlocutor. As part of the study of pragmatics, illocutionary speech acts include various forms of speech, such as commands, requests, suggestions, promises, and expressions of feelings conveyed in certain contexts. Films as a representation of life present communication dynamics that are rich in meaning, where the characters’ speaking styles not only function as communication tools, but also reflect identity and social relations. The character Dilan in this film is known to have a unique way of communicating full of subtle allusions, humor, and implied meanings that reflect his attitude and communicative strategies in establishing relationships with Milea and other characters. Thus, this study aims to identify and classify the illocutionary speech acts used by Dilan, as well as to understand how his language choices contribute to shaping the dynamics of interaction and characterization in the film. The main data in this study are Dilan’s dialogue transcripts, which are analyzed based on Searle’s speech act categories, namely assertive, directive, commissive, expressive, and declarative. The results of the study show that directive and assertive are the speech acts most often used by Dilan, with speech forms dominated by invitations, mild sarcasm, and statements of belief packaged with humor. In addition, commissives often appear in the form of promises or commitments to Milea, which shows the intensity of the relationship between the two characters. Expressives function to convey emotions indirectly, while declaratives play a greater role in shaping Dilan’s social identity in his social environment. The diversity of these speech acts reflects the typical communication patterns of adolescents, where language is not only used as a means of self-expression, but also as a tool to build social relationships and create a certain impression in front of the interlocutor.